PRINCIPLES OF ASSET VALUATION. - Daniels, Mortimer B. (The Accounting Review, 1934)
Abstract The primary purpose of accounting is to measure income, and income is the difference between cost and revenue. It follows that the valuation basis for assets which represent future expenses should be actual cost. When unrecovered costs which are also deferred charges to future operations are set up on the books at appraised values, either higher or lower than actual cost, expense in subsequent accounting periods until such unrecovered costs have been properly charged against revenues will reflect to a certain extent fictitious amounts rather than actual cost. This applies to inventories, when based on the popular cost or market formula, and to buildings, equipment, and intangible plant assets, such as patents. In short, it is not conservative to write down the balance sheet valuations of depreciable and amortizable assets below bonafide cost inasmuch as this results in showing a portion of future expense, depreciation and amortization, at less than actual cost, thereby inflating profits.